Phenotypic and Genotypic Antimicrobial Resistance in Non-O157 Shiga Toxin-Producing Escherichia coli Isolated From Cattle and Swine in Chile - Galarce, Nicolás; Sánchez, Fernando; Fuenzalida, Verónica; Ramos, Romina; Escobar, Beatriz; Lapierre, Lisette; Paredes-Osses, Esteban; Arriagada, Gabriel; Alegría-Morán, Raúl; Lincopán, Nilton; Fuentes-Castillo, Danny; Vera-Leiva, Alejandra; et al. (Frontiers in Veterinary Science, 2020)
Non-O157 Shiga toxin-producing Escherichia coli (STEC) is a zoonotic pathogen that causes bloody diarrhea and hemolytic-uremic syndrome in humans, and a major cause of foodborne disease. Despite antibiotic treatment of STEC infections in humans is not recommended, the presence of antimicrobial-resistant bacteria in animals and food constitutes a risk to public health, as the pool of genes from which pathogenic bacteria can acquire antibiotic resistance has increased. Additionally, in Chile there is no information on the antimicrobial resistance of this pathogen in livestock. Thus, the aim of this study was to characterize the phenotypic and genotypic antimicrobial resistance of STEC strains isolated from cattle and swine in the Metropolitan region, Chile, to contribute relevant data to antimicrobial resistance surveillance programs at national and international level. We assessed the minimal inhibitory concentration of 18 antimicrobials, and the distribution of 12 antimicrobial resistance genes and class 1 and 2 integrons in 54 STEC strains. All strains were phenotypically resistant to at least one antimicrobial drug, with a 100% of resistance to cefalexin, followed by colistin (81.5%), chloramphenicol (14.8%), ampicillin and enrofloxacin (5.6% each), doxycycline (3.7%), and cefovecin (1.9%). Most detected antibiotic resistance genes were dfrA1 and tetA (100%), followed by tetB (94.4%), blaTEM-1 (90.7%), aac(6)-Ib (88.9%), blaAmpC (81.5%), cat1 (61.1%), and aac(3)-IIa (11.1%). Integrons were detected only in strains of swine origin. Therefore, this study provides further evidence that non-O157 STEC strains present in livestock in the Metropolitan region of Chile exhibit phenotypic and genotypic resistance against antimicrobials that are critical for human and veterinary medicine, representing a major threat for public health. Additionally, these strains could have a competitive advantage in the presence of antimicrobial selective pressure, leading to an increase in food contamination. This study highlights the need for coordinated local and global actions regarding the use of antimicrobials in animal food production.